2019
DOI: 10.1007/s41465-019-00135-6
|View full text |Cite
|
Sign up to set email alerts
|

Transfer and Motivation After Cognitive Control Training for Remitted Depression in Healthy Sample

Abstract: Objective: Given that cognitive control deficits following remission from depression form a risk factor for recurrence, new interventions aimed at improving cognitive control such as cognitive control training, are being developed. Previous studies suggest that motivation and engagement can influence effectiveness of cognitive training. As such, we developed a gamified cognitive control training procedure. Before validating this tool in a clinical sample, a convenience sample was used to ensure that gamificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 72 publications
5
14
1
Order By: Relevance
“…In particular, a discrepancy between the CCT and ACT condition seemed to develop around the period of 3 months after the intervention. This is in line with recent findings suggesting a delayed effect of CCT on depressive symptoms in RMD patients (e.g., Vervaeke et al, 2020). On the basis of the obtained cutoff for the weekly ratings, estimated recurrence rates were 31.82% in the CCT condition compared with 51.22% in the ACT condition.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In particular, a discrepancy between the CCT and ACT condition seemed to develop around the period of 3 months after the intervention. This is in line with recent findings suggesting a delayed effect of CCT on depressive symptoms in RMD patients (e.g., Vervaeke et al, 2020). On the basis of the obtained cutoff for the weekly ratings, estimated recurrence rates were 31.82% in the CCT condition compared with 51.22% in the ACT condition.…”
Section: Discussionsupporting
confidence: 93%
“…This may be due to overlap between the domains of influence of both training procedures (i.e., potentially affecting broader attentional processes). This result is in line with a recent replication study providing mixed evidence for the emotional transfer effects of aPASAT training compared with a similar active control training in RMD patients (Vervaeke et al, 2020). That is, in contrast to Hoorelbeke and Koster (2017), Vervaeke and colleagues (2020) did not observe beneficial effects of aPASAT training on self-reported emotion regulation or resilience over a 6-month follow-up period.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It has been shown that the effectiveness of cognitive training can be increased due to involvement in activities and increased motivation through learning cognitive control using play procedures or nonplay learning [51]. Improving visual memory is possible through the application of a strategy for controlling attention and directing it to target memory components [40].…”
Section: Groupmentioning
confidence: 99%